Edukasi Perencanaan dan Penganggaran Keuangan untuk Penguatan UMKM di Kelurahan Paninggilan, Ciledug - Hafizh, Abdul; A, Aprida; Simatupang, Lusiana Fransiska; Nuraini, Saroyah; Widiyati, Dian (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Good financial management is an important factor for the sustainability of micro, small, and medium enterprises (MSMEs). This Community Service Program (PKM) aims to provide financial planning and budgeting education to MSME actors in Paninggilan Village, Ciledug. The methods used include initial surveys, training in the use of simple financial management applications, implementation assistance, and evaluation and monitoring. The results of the activities show an increase in understanding and ability of MSME actors in recording financial transactions and preparing budgets in a planned manner. Intensive assistance helps participants overcome practical obstacles in financial management. Although there are challenges related to digital literacy and limited resources, this program has proven effective in strengthening MSME financial management so that it can increase competitiveness and business sustainability. Continuous education and adjustment of programs to field needs are recommended to support optimal MSME development.